2013
DOI: 10.1016/j.molonc.2013.01.006
|View full text |Cite
|
Sign up to set email alerts
|

How animal models of leukaemias have already benefited patients

Abstract: The relative genetic simplicity of leukaemias, the development of which likely relies on a limited number of initiating events has made them ideal for disease modelling, particularly in the mouse. Animal models provide incomparable insights into the mechanisms of leukaemia development and allow exploration of the molecular pillars of disease maintenance, an aspect often biased in cell lines or ex vivo systems. Several of these models, which faithfully recapitulate the characteristics of the human disease, have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 77 publications
1
3
0
Order By: Relevance
“…Both studies highlight the importance of a humanized microenvironment for studying human leukemic niches in animals; however, technical advances are still required in order to achieve an identical human immune function in recipient animals (e.g., HLA alleles matched to donor human cells, development of lymphoid architecture, identification of human-specific factors needed for optimal human cell function that are absent in mice, among others). It is also necessary to prevent the development of graft vs. host disease, which occurs in many of the human immune engrafted models, and validate the results obtained in the models described here [146,157].…”
Section: In Vivo Rodent Modelssupporting
confidence: 53%
“…Both studies highlight the importance of a humanized microenvironment for studying human leukemic niches in animals; however, technical advances are still required in order to achieve an identical human immune function in recipient animals (e.g., HLA alleles matched to donor human cells, development of lymphoid architecture, identification of human-specific factors needed for optimal human cell function that are absent in mice, among others). It is also necessary to prevent the development of graft vs. host disease, which occurs in many of the human immune engrafted models, and validate the results obtained in the models described here [146,157].…”
Section: In Vivo Rodent Modelssupporting
confidence: 53%
“…Mice can be genetically engineered to express dominant oncogenes in the mouse germline or by mutation of tumor suppressor genes. AML was amongst the earliest diseases to be modelled using transgenic animals owing to its relative genetic simplicity [ 219 , 220 ]. Transgenic models can be produced by several methods and have been reviewed elsewhere [ 221 ].…”
Section: Models Of Acute Myeloid Leukemiamentioning
confidence: 99%
“…Notably, another classical transgenic model for APL associated with a PLZF-RARA fusion gene derived from t(11;17)(q23;q21) revealed that ATRA was unable to induce remission in mice, faithfully recapitulating the clinical response in the respective patients [55]. We list some of the most important classical transgenic AML models in Table 1 and refer to respective review articles [56,57,58]. Unfortunately, the classical transgenic mouse approach is inefficient, technically challenging, time- and cost-consuming and as illustrated by the APL mouse model and others, unable to recapitulate the desired phenotypes [59].…”
Section: Genetically Engineered Mouse Modelsmentioning
confidence: 99%